2010
DOI: 10.1074/jbc.m110.165506
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Ras Association Domain Family 5 (RASSF5/NORE1) Mediates Death Receptor Ligand-induced Apoptosis

Abstract: Epigenetic silencing of RASSF (Ras association domain family) genes RASSF1 and RASSF5 (also called NORE1) by CpG hypermethylation is found frequently in many cancers. Although the physiological roles of RASSF1 have been studied in some detail, the exact functions of RASSF5 are not well understood. Here, we show that RASSF5 plays an important role in mediating apoptosis in response to death receptor ligands, TNF-␣ and TNF-related apoptosis-inducing ligand. Depletion of RASSF5 by siRNA significantly reduced TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 43 publications
2
86
0
Order By: Relevance
“…4), the regulation of the upstream signaling of MST1/2 by netrin-1 is not excluded. Moreover, RASSF5 plays an important role in mediating apoptosis in response to death receptor ligands (31). Thus, netrin-1, as the ligand of dependence receptors, through up-regulation of YAP activity, may exert the antagonistic action against RASSF.…”
Section: Discussionmentioning
confidence: 99%
“…4), the regulation of the upstream signaling of MST1/2 by netrin-1 is not excluded. Moreover, RASSF5 plays an important role in mediating apoptosis in response to death receptor ligands (31). Thus, netrin-1, as the ligand of dependence receptors, through up-regulation of YAP activity, may exert the antagonistic action against RASSF.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells from the Rassf5a À/À mice were resistant to TNFa and TRAIL-dependent cell death and reduced activation of JNK kinases in response to TNFR stimulation failed to activate MST1 in vivo [80]. In line with the role of RASSF5 as a tumor suppressor, K-Ras transfected mouse embryonic fibroblasts developed a significant amount of tumors when injected into immune compromised mice to support the role of RASSF5 in restricting excessive growth [80]. Recently it was demonstrated that RASSF5A plays a role in developing the nervous system [83].…”
Section: Rassf5mentioning
confidence: 99%
“…The C57BL/6-Rassf5a À/À mice were just recently generated but do not have an overt phenotype nor evidence of tumor formation as they age [80]. However, cells from the Rassf5a À/À mice were resistant to TNFa and TRAIL-dependent cell death and reduced activation of JNK kinases in response to TNFR stimulation failed to activate MST1 in vivo [80].…”
Section: Rassf5mentioning
confidence: 99%
See 2 more Smart Citations